Implementasi Teknologi Pengolah Limbah Sabut Kelapa Menjadi Cocofiber dan Cocopeat di Desa Lenteng Timur, Sumenep - Saputro, Wiliandi; Faizin, Ahmad Khairul; Sari, Tria Puspa (Universitas Muhammadiyah Surakarta, 2023)
Coconut is one of the leading commodities of plantation crops for the community in East Lenteng Village, Sumenep Regency, East Java. Based on data from the Central Statistics Agency, the area of ​​coconut plantations in Lenteng District reaches 3114 ha. Generally, the use of coconut plants by the local community only extracts coconut water and flesh, resulting in waste in the form of coconut coir in the amount of 910 tons. Therefore, finding innovative and effective solutions to process the coconut coir waste into superior products with benefits and economic value. This community service activity aims to process coconut coir waste into derivative products in the form of cocofiber and cocopeat. Later, cocofiber and cocopeat are used as basic materials for filling mattresses, pillows, and planting media that can provide added value. The implementation method consisted of direct field observations, formulation of problems and solutions, data collection of coco fiber samples, processing of coconut coir waste, application of science and technology, and evaluation. Based on the results of performed activities, the residents of East Lenteng Village can discover the process of processing coconut coir waste into cocofiber and cocopeat. In addition, the residents of East Lenteng Village also gain knowledge regarding using more practical and efficient processing machines of coconut coir waste. Based on the test results of the processing machine of coconut coir waste, the measured capacity of cocopeat production reaches 3 kg/hour while cocofiber reaches 1 kg/hour.